2019
DOI: 10.3389/fphys.2019.01537
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Exercise Training Counteracts Muscle Disuse and Attenuates Reductions in Physical Function in Individuals With Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease, characterized by the progressive loss of motor neurons, which leads to a reduction in strength and exercise capacity. Although the concept of "Exercise is Medicine" is accepted for many diseases, the role of exercise in individuals with ALS is still debated. The aim of this study was to propose a tailored exercise training program that was both safe and effective for individuals with ALS, and to evaluate the effects of this combined, moderatei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 31 publications
(37 reference statements)
0
24
0
5
Order By: Relevance
“…It was also observed that there were scores on the functionality scale that decreased more than in the rest of the studies that carried out the measurement at 3 months and that their cases and controls obtained very different results, since the points in the usual care control patients dropped from 35 to 23 and dropped from 40 to 35 in the motor rehabilitation patients. However, this can be justified with the fact that they started with 40 points, significantly more than the controls [12]. Regarding the large drop in this study in just 3 months in the score on the ALSFRS-R scale, it could be reflected on whether the age of the patients in this trial had an influence compared to the rest, since the mean age in this study was 53 and 61 in the other studies (Table 2).…”
Section: Medium-term Effectsmentioning
confidence: 64%
See 3 more Smart Citations
“…It was also observed that there were scores on the functionality scale that decreased more than in the rest of the studies that carried out the measurement at 3 months and that their cases and controls obtained very different results, since the points in the usual care control patients dropped from 35 to 23 and dropped from 40 to 35 in the motor rehabilitation patients. However, this can be justified with the fact that they started with 40 points, significantly more than the controls [12]. Regarding the large drop in this study in just 3 months in the score on the ALSFRS-R scale, it could be reflected on whether the age of the patients in this trial had an influence compared to the rest, since the mean age in this study was 53 and 61 in the other studies (Table 2).…”
Section: Medium-term Effectsmentioning
confidence: 64%
“…Some of the therapeutic physical exercise interventions consisted of aerobic exercise [9,10], moderate-high intensity strength and endurance exercises [5,[11][12][13], functional training or stretching [14,15]. Frequencies ranged from highest to lowest [10] according to the study, and the intervention time was a minimum of 2 weeks and a maximum of 6 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the data have highlighted the need to adapt the type and intensity of physical activity to each patient. For instance, Ferri and colleagues showed that a training program combining moderate-intensity aerobic and strength training improved the patients’ aerobic capacity and physical function when tailored to their individual needs [ 220 ].…”
Section: Physical Exercise As a Therapeutic Approachmentioning
confidence: 99%